Translanguaging strategies in multimodality and audiovisual translation. Issue 1 (2nd January 2021) - Tomei, Renato; Chetty, Rajendra
Abstract: Translanguaging practices are firmly embedded in South African communication practices given the country's high levels of linguistic diversity. This approach represents a challenge to the institutional and educational system in the current decolonial discourse where English serves as the dominant language. The critical analysis of the relationship between translanguaging and translation resonates with recent studies in the domain of applied linguistics and language practice. This article aims at highlighting the practical implications of the use of translanguaging strategies in the subfield of multimodal and audiovisual translation, through the analysis of the cinematic adaptations of Alan Paton's Cry, the Beloved Country, and Joshua Sinclair's Shaka Zulu . The analysis suggests that linguistic normalisation, cultural substitution, domestication, and also the addition and deletion of isiZulu words, can foster discrepancy of communication, and generate macro-textual modifications, as in the case of identity markers. The field of language practice can benefit from a more careful consideration of the value and advantages of the translanguaging approach, posing critical questions regarding the actual need for translation.